Strukturasi Media Daerah dalam Regulasi di Era Konvergensi dan Disrupsi - Hariyani, Nunik; Wahyuni, Hermin Indah; Budiman, Christian (Universitas Merdeka Madiun, 2018)
This research moves from the reality of media life of area in Madiun of East Java which experiencing changes in line with social politics situation of Indonesia. Media is a commodity that can be exchanged, it is exploit all the potential and various social forces that exist. This study aims to know and analyze the stuctutation of regional mass media, the weekly magazine of Kridha Rakyat in Madiun, East Java. The theory used is the political economy approach that is the structuration according to Vincent Mosco. The method used is descriptive qualitative with data collection technique through interview, observation, ethnography and content analysis. The results show that the media perform the process of production and reproduction of power structures by media rulers (owner) by utilizing media agents and social relationship with other structure outside media. The media produces a series of power-reinforcing powers that ultimately reinforce the media's position.